CAD-RADS may underestimate coronary plaque progression as detected by serial CT angiography . (23rd October 2021) - Szilveszter, Bálint; Vattay, Borbála; Bossoussou, Melinda; Vecsey-Nagy, Milán; Simon, Judit; Merkely, Béla; Maurovich-Horvat, Pál; Kolossváry, Márton
Abstract: Aims: We wished to assess whether different clinical definitions of coronary artery disease (CAD) [segment stenosis and involvement score (SSS, SIS), Coronary Artery Disease—Reporting and Data System (CAD-RADS)] affect which patients are considered to progress and which risk factors affect progression. Methods and results: We enrolled 115 subsequent patients (60.1 ± 9.6 years, 27% female) who underwent serial coronary computed tomography angiography (CTA) imaging with >1year between the two examinations. CAD was described using SSS, SIS, and CAD-RADS. Linear mixed models were used to investigate the effects of risk factors on the overall amount of CAD and the effect on annual progression rate of different definitions. Coronary plaque burdens were SSS 4.63 ± 4.06 vs. 5.67 ± 5.10, P < 0.001; SIS 3.43 ± 2.53 vs. 3.89 ± 2.65, P < 0.001; CAD-RADS 0:8.7% vs. 0.0% 1:44.3% vs. 40.9%, 2:34.8% vs. 40.9%, 3:7.0% vs. 9.6% 4:3.5% vs. 6.1% 5:1.7% vs. 2.6%, P < 0.001, at baseline and follow-up, respectively. Overall, 53.0%, 29.6%, and 28.7% of patients progressed over time based on SSS, SIS, and CAD-RADS, respectively. Of the patients who progressed based on SSS, only 54% showed changes in CAD-RADS. Smoking and diabetes increased the annual progression rate of SSS by 0.37/year and 0.38/year, respectively (both P < 0.05). Furthermore, each year increase in age raised SSS by 0.12 [confidence interval (CI) 0.05–0.20, P = 0.001] and SIS 0.10 (CI 0.06–0.15, P < 0.001), while female sex was associated with 2.86 lower SSS (CI −4.52 to −1.20, P < 0.001) and 1.68 SIS values (CI −2.65 to −0.77, P = 0.001). Conclusion: CAD-RADS could not capture the progression of CAD in almost half of patients with serial CTA. Differences in CAD definitions may lead to significant differences in patients who are considered to progress, and which risk factors are considered to influence progression. Graphical Abstract: